INFLUENCE OF ELECTRODE TYPE ON THE MECHANICAL PROPERTIES OF THE RESULT AISI 1018 STEEL SMAW WELDING - Deny Wakhyudi; Kisto (Magister Teknik Mesin Universitas Pancasila, 2026)
The mechanical and physical characteristics of a welded joint are greatly influenced by the choice of electrode type and the applied current. Therefore, this research was conducted to evaluate the impact of these two variables on specimen performance, which includes macro-micro review, hardness mapping, and tensile strength. Experiments were conducted using the Shielded Metal Arc Welding (SMAW) method on AISI 1018 steel material with a constant welding rate. The test involved three electrode variants (E6013, E7016, and E7018) combined with three current levels (70A, 110A, and 130A). Based on the analysis results, it was proven that the current plays a vital role in changing material properties. An inverse correlation was found: increasing the welding current consistently triggered a decrease in both hardness and tensile strength. Regarding the comparison between electrodes, the most optimal hardness level reached 105 HRB obtained from the combination of the E7018 electrode with a current setting of 70A. On the other hand, the maximum tensile strength was recorded at 34.697 MPa, which was produced through the use of E6013 electrodes at a current strength of 110A.